Promoting transparency in the NGO sector: Examining the availability and reliability of self-reported data - Ronelle Burger; Trudy Owens (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2008)
Amid widespread calls for NGOs to become more accountable and transparent, this work examines the prevalence of discrepancies between what NGOs say and what they do. It does so using a unique dataset of 300 NGOs in Uganda with corresponding beneficiary assessments. Investigating NGO dishonesty with regards to financial transparency and community participation, the study finds a high incidence of misrepresentation among NGOs. Results from a Heckman probit model suggest that the determinants of misrepresentation differ according to the subject matter: the threat of being caught reduces the likelihood of dishonesty about financial transparency, while a desire to `save face' to maintain a good reputation appears to be the main motivator of a misrepresentation of community. consultation. The analysis provides tentative indications that NGOs with antagonistic relations with the government may be more likely to hide information and be dishonest. It also lends some support to the view that excessive and unrealistic donor demands may be an obstacle to openness and transparency. The findings of this work caution against an overly naïve and simplistic view of NGOs, and specifically, an overreliance on reported information when regulating, monitoring or surveying NGOs.
Keywords: 330; Nichtregierungsorganisation; Politisches Ziel; Selbstverpflichtung; Unvollkommene Information; Uganda